Comparative Seismic Performance of Flat Slab-Drop Panel and Conventional Slab Systems for Hospital Buildings - Putu Didik Sulistiana; I Putu Pranayoga Aditya; I Gusti Agung Putu Eryani (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2026)
Hospitals are classified as essential facilities and therefore require adequate seismic performance to maintain structural safety during earthquake events. This study compares the seismic performance of a conventional slab system and a flat slab-drop panel (FSDP) system in a four-story reinforced concrete hospital building using the Response Spectrum Analysis (RSA) method. Two three-dimensional structural models were developed in ETABS v21.2 with identical geometry, material properties, loading conditions, and boundary conditions. The only variable considered was the floor system configuration. Structural responses, including structural weight, fundamental period, inter-story drift, slab deflection, base shear, and column reinforcement demand, were evaluated in accordance with SNI 1726:2019 and SNI 2847:2019. The results indicate that the FSDP system increased the total structural weight by 6.54%, the fundamental period by 30.2% and 18.2% in the X- and Y-directions, respectively, and the base shear by 42.29% and 26.85%. In addition, the FSDP system produced larger inter-story drift, slab deflection, and column design demand than the conventional slab system. Nevertheless, all evaluated structural responses satisfied the design requirements specified in the applicable Indonesian standards. Overall, the conventional slab system was found to be more structurally efficient, exhibiting lower inter-story drift, slab deflection, base shear, and column reinforcement demand than the FSDP system, while both structural systems satisfied the seismic design requirements specified in SNI 1726:2019 and SNI 2847:2019. The FSDP system, however, offers greater architectural flexibility and construction efficiency.